Cogent synergic effect of TiS2/g-C3N4 composite with enhanced electrochemical performance for supercapacitor. Issue 17 (1st December 2020) - Nabi, Ghulam; Riaz, Khalid Nadeem; Nazir, Maria; Raza, Waseem; Tahir, Muhammad Bilal; Rafique, Muhammad; Malik, Nafisa; Siddiqa, Ayesha; Ali Gillani, S. Sajid; Rizwan, Muhammad; Shakil, Muhammad; Tanveer, Muhammad
Abstract: The demand of composite materials with enhanced electrochemical performance for supercapacitors is emerging. With the aim to improve the electrochemical performance, g-C3 N4, TiS2 and TiS2 /g-C3 N4 composite have been synthesized by a facile hydrothermal approach. The structure and surface morphology of the synthesized materials were analyzed by using X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive X-rays spectroscopy (EDS). The electrochemical performance of TiS2 and TiS2 /g-C3 N4 composites were studies by using three electrode system in 2 M KOH electrolyte. The TiS2 /g-C3 N4 micro-composite showed the higher specific capacitance (546 F/g) as compared to TiS2 (292 F/g) and g-C3 N4 (200–300 F/g) due to smaller size, additional active sites and strong synergic effect. More than 87% of the capacitance was retained after 2500 cycles, demonstrating the splendid cyclic stability of the composite. The improved specific capacitance and long cyclic stability of TiS2 /g-C3 N4 micro-composites shows that this composite material is promising for supercapacitor electrodes.